PENGEMBANGAN E-LKPD BERBASIS KOMIK PADA PEMBELAJARAN IPAS DIKELAS V SEKOLAH DASAR - Gumala Dewi, Sri Putri; Yeni Erita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
his research aims to develop a Comic-Based E-LKPD for IPAS learning in Class V Elementary School that is valid, practical, and effective. The research is motivated by the lack of use of attractive E-LKPD and teacher skills in using digital-based ELKPD. This research uses Research & Development, and the development model used is the ADDIE model. The results show that the developed E-LKPD has a material validity level of 80%, media validity of 87.5%, and language validity of 82.5%. The teacher questionnaire results at SDN 01 Pasar Tiku were 93.75% in the very practical category, while the student response questionnaire was 89.38% in the very practical category. At SDN 14 Banda Gadang, the teacher questionnaire was 96.87% in the very practical category, and the student questionnaire was 84.61% in the very practical category. Additionally, the research schools SDN 20 Pasar Tiku, SDN 05 Pasar Tiku, and SDN 25 Pasir Tiku also showed positive results, with teacher questionnaires ranging from 90.62% to 93.75% in the very practical category, and student questionnaires ranging from 79.62% to 93.40% in the practical to very practical category. The effectiveness results showed significant improvements, with the first trial school SDN 01 Pasar Tiku increasing from 69.3% to 89.9% in the very effective category, and the second trial school SDN 14 Banda Gadang increasing from 70.8% to 90.0% in the very effective category. Similarly, the research schools also showed improvements, with SDN 20 Pasar Tiku increasing from 67.7% to 87.2%, SDN 05 Pasar Tiku increasing from 69.2% to 84.2%, and SDN 25 Pasir Tiku increasing from 65% to 82.9%, all in the very effective category. Therefore, it can be concluded that the Comic-Based E-LKPD for IPAS learning in Elementary School has been declared valid, practical, and effective.